PERBANYAKAN Corcyra cephalonica Stainton (Lepidoptera : Pyralidae) PADA BERBAGAI KOMPOSISI MEDIA - Aprilidia R Rajagukguk; Maryani Cyccu Tobing; Yuswani Pangestiningsih (Universitas Sumatera Utara, 2013)
ABSTRACTMass rearing of Corcyra cephalonica Stainton (Lepidoptera : Pyralidae) in Several Media. Thestored pest C. cephalonica is one of alternative host Trichogramma spp. This research was to studyto find the best feed for mass rearing C. cephalonica as an alternative host Trichogramma spp. Thisresearch was carried out at Central Research and Development of Sugarcane Crop Sei SemayangPTPN II Medan since July-September 2012. The method of used Randomized Complete Designwhich consists 22 treatments and two replication. The results showed that the combination of ricebran and mill maize is the best treatment. The day early that the adult emerge fastest in media ricebran and mill maize with comparison 1:2 is 32.5 days after application and the lowest in mediamaize bran and chicken feed with comparison 1:1, 1:2, 2:1 is 48 days after aplication.The highest number of imago in media rice bran and mill maize with comparison 1:2 is338.5 adults and the lowest in media mill maize and chicken feed is 68.5 adults. The sex ratioof male and female is 1:1Keywords: Media, Corcyra cephalonica, mass rearing